Impatient Balsamina as Agribusiness Commodity in Bali - Ni Putu Sukanteri (SEAS (Sustainable Environment Agricultural Science), 2023)
Impatient balsamina is one of the agricultural commodities that is mass-cultivated on the island of Bali, and the use of inpatient balsamina flowers as religious and cultural facilities in the community in Bali. So that the impatient balsamina agribusiness community is able to provide a decent income for farmers and marketing institutions, the purpose of the research is to find out the efficiency of impregnated balsamina marketing in Bali and to know the impatient balsamina marketing channel. Agribusiness impatiens balsamina becomes one of the interesting phenomena to be studied because marketing is mostly marketed in traditional markets in big cities in Bali such as in the traditional markets of Denpasar. The main consumers of impatient balsamina are urban people living in cities on the island of Bali. The results showed that the elasticity of marketing transmission of impatient balsamina commodities amounted to 1,143, this shows if Et> 1, then the rate of change in prices at the producer level. The market faced by all market participants is imperfect actors, that is, there is monopoly and oligopoly power in the marketing system and the marketing system is not yet efficient. Impatient balsamina production give marketing channels are farmers, traders, wholesalers, retailers, consumers